Current state of the source of evidence in the form of testimony of the accused - Bachurin, S.N.; Kussainova, L.K.; Kalmaganbetova, D.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This scientific article examines certain issues of the current state of the source of evidence in the form of testimony of the accused. Scientific interest has been aroused in this issue against the backdrop of the construction of a new three-tier model of judicial and law enforcement activities, providing for maximum respect for the rights and legitimate interests of citizens. The current state of the legal norms governing applications in criminal proceedings is analyzed in abstract form, especially at the stage of completion of the pre-trial investigation and in relation to such an active participant in the criminal process as the accused, in terms of correlation with the rules of evidence. Of particular interest in the scientific article is the presence of a legislative situation in which such a source of evidence as the testimony of the accused has actually dropped out of the system of sources of evidence, despite its formal presence as such among the factual data relevant for the correct resolution of a criminal case. Situations in the current legislation are analyzed in which there is a discrepancy with the previously theoretical interpretation of the rules on evidence, but which make it possible to identify new theoretical solutions that allow resolving such inconsistencies in the provisions of the current norms of the Criminal Procedure Code of the Republic of Kazakhstan, preserving the current system of sources of evidence or justifying a new position in terms of using the testimony of the accused as a source of evidence in modern realities.